Model for prevention and control of hand, foot and mouth disease (HFM) in the community - เลิศสุโภชวณิชย์, สมนึก; หงษ์สามสิบหก, ณัฐทิชา; ผดุงหมาย, มัลลิกา; เจริญไทย, กรรณิการ์; นาคอ้าย, วรยุทธ (Disease Control Journal, 2018)
Hand, Foot and Mouth Disease (HFM) is one of the significant public health problems. There have been reports of severe HFM outbreaks caused by enterovirus 71 in various countries including Thailand. The disease is most prevalent among children aged under 5 years. Outbreaks commonly occurred in places where a large number of children were gathering such as nurseries, kindergartens and community centers. This document analysis aimed to synthesize and develop the model for HFM prevention and control that is suitable for community context by systematic literature review. A total of 554 scientific documents, articles, and research papers were included from electronic databases locally and internationally available online during 2001-2018. Of these, 46 papers that met the criteria were selected for content analysis. Analysis and synthesis of findings from relevant research reports conducted in Thailand and other countries to develop appropriate model for HFM prevention and control at the community level suggested that the model be comprised of 3 components, namely human factors or individual prevention, family factors or household and community preventions, and macro factors or social preventions. To apply the model in a given community, it is necessary that it be adapted in accordance with its socio-cultural contexts to determine and design the activities suitable for the community.